Effect of Additional Factors on Dimensional Accuracy and Surface Finish of Turned Parts - Islam, Mohammad Nazrul (Taylor and Francis, 2013)
This paper reports the experimental and analytical results of an investigation of additional factors that affect the dimensional accuracy and surface finish of turned parts besides the three major cutting parameters—cutting speed, feed rate, and depth of cut. The selected additional factors were cooling method, blank size, and work material. A three-level, three-parameter experiment was planned using design-of-experiment methodology. The three levels of independent input parameters were: for cooling method—dry turning, flood turning, and minimum quantity lubrication turning; for blank size— Ф20, 40, and 60 mm; and for work material—aluminium 6061, mild steel 1030, and alloy steel 4340. The measured output parameters were the two most widely used dimensional accuracy characteristics of turned parts—diameter error and circularity—and the surface finish characteristic arithmetic average. The results were analysed applying three methods: traditional analysis, Pareto ANOVA, and Taguchi method. The results reveal that, while work material has the greatest effect on diameter error and surface roughness, the major contributor to circularity is blank size.